A high-resolution H I study towards the supernova remnant Puppis A and its environments - Reynoso, E.; Cichowolski, S.; Walsh, Andrew (Oxford University Press, 2017)
We observed the supernova remnant Puppis A in the 21 cm line with the Australia Telescope Compact Array with the aim of determining the systemic velocity and, hence, the corresponding kinematic distance. For the compact, background sources in the field, we obtain absorption spectra by applying two methods: (a) subtracting profiles on- and off-source towards continuum emission, and (b) filtering short spacial frequencies in the Fourier plane to remove large-scale emission. One of the brightest features to the east of the shell of Puppis A was found to be a background source, probably extragalactic. Removing the contribution from this and the previously known unrelated sources, the systemic velocity of Puppis A turns out to be limited between 8 and 12 km s−1, which places this source at a distance of 1.3 ± 0.3 kpc. From the combined images that include both single-dish and interferometric data, we analyse the distribution of the interstellar hydrogen. We suggest that an ellipsoidal ring at v ∼ +8 km s−1 could be the relic of a bubble blown by the progenitor of Puppis A, provided the distance is ≲ 1.2 kpc. The main consequences of the new systemic velocity and distance as compared with previous publications (v = +16 km s−1 and d = 2.2 kpc) are the absence of a dense interacting cloud to the east to explain the morphology, and the decrease of the shell size and the neutron star velocity, which are now in better agreement with statistical values.